Conversation of Our Lord and Saviour Jesus with His Twelve Apostle Disciples at Jericho (EMML 7229, fols 93r–109r) - Getatchew Haile (Aethiopica, 2021)
The article presents a collation and translation of an apocalyptic text, which may be titled, Conversation of Our Lord and Saviour Jesus with His Twelve Apostle Disciples at Jericho, as taken from EMML 7229, fols 93r–109r. It is one of the two conversations known so far (the other took place at Däbrä Zäyt) and, although copied in the same hand, this conversation cannot be considered a part of the traditional Nägärä Maryam.